The Destruction of Cultural Property in the Syrian Conflict: Legal Implications and Obligations. Issue 1 (3rd March 2016) - Cunliffe, Emma; Muhesen, Nibal; Lostal, Marina
Abstract: This article comes as the conflict in Syria has entered its fifth year, bringing with it loss of life and the displacement of the Syrian people as well as extensive damage to, and destruction of, the country's cultural heritage. This article will first provide an overview and explanation of the national and international legal framework for protecting cultural property in conflict as it applies to the Syrian State and the non-State actors involved, using examples from the whole conflict, including the recent actions of Da'esh. Second, we demonstrate that the destruction of all types of cultural property, regardless of its importance, can be considered a prosecutable violation of these laws, and we examine the possibilities for prosecution. Following from this discussion, we question whether the existing framework can be considered effective and consider the role the international heritage community can play.